Stoichiometric Combustion Modeling and Regulatory Compliance Assessment of Indonesian Sub-bituminous Coal: Implications for Clean Coal Technology Deployment - Robekca Purba; Nyimas Ulfatry Utami (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2026)
Coal is an important energy source, but its utilization must consider quality and environmental aspects for sustainability. This study aims to characterize coal from Muara Enim Regency and to evaluate its energy utilization potential. A 2.365 kg coal sample was analyzed at Geoservice laboratory, Bandung. Proximate analysis results showed total moisture 6.26%, ash content 10.63%, volatile matter 37.84%, and fixed carbon 47.71%. Ultimate analysis revealed carbon 68.56%, hydrogen 5.12%, nitrogen 1.42%, oxygen 13.71%, and sulfur 0.56%. The calorific value is 6,900 kcal/kg with fuel ratio 1.26. These parameters classify the coal as Sub-bituminous B with good combustion characteristics. Stoichiometric calculations determined theoretical air requirements of 2.24 kg/kg coal, producing 2.51 kg CO₂, 0.46 kg H₂O, 0.0009333 kg NO2 and 0.0112 kg SO₂. Theoretical SO₂ emissions (1.557 mg/Nm³) exceed Indonesian regulations, requiring Flue Gas Desulfurization (FGD) installation. The coal has good energy potential with low sulfur content, suitable for power generation with proper emission control technology. This study provides a database for optimizing energy systems and clean coal technologies..Keywords: coal characterization; calorific value; combustion stoichiometry; clean coal technology, coal chemistry